2013
DOI: 10.1159/000356360
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and Memory in Borderline Personality Disorder

Abstract: Memory processes such as encoding, storage, and retrieval of information are influenced by emotional content. Because patients with borderline personality disorder (BPD) are particularly susceptible to emotional information, it is relevant to understand whether such memory processes are altered in this patient group. This systematic literature review collects current evidence on this issue. Research suggests that emotional information interferes more strongly with information processing and learning in BPD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 144 publications
(212 reference statements)
4
23
0
Order By: Relevance
“…In anxiety disorders, however, the evidence for memory bias is mixed (Mathews & MacLeod, ; Mitte, ). Furthermore, some recent studies found evidence for memory bias in disorders other than depression and anxiety, e.g., borderline personality disorder (Winter, Elzinga, & Schmahl, ), eating disorders (Nikendei et al., ), and schizophrenia (Peters, Hauschildt, Moritz, & Jelinek, ). The association between memory bias and psychiatric comorbidity is unclear at this point, but negative emotions are a key aspect of not only depression and anxiety, but of many psychiatric disorders (American Psychiatric Association, ).…”
Section: Introductionmentioning
confidence: 99%
“…In anxiety disorders, however, the evidence for memory bias is mixed (Mathews & MacLeod, ; Mitte, ). Furthermore, some recent studies found evidence for memory bias in disorders other than depression and anxiety, e.g., borderline personality disorder (Winter, Elzinga, & Schmahl, ), eating disorders (Nikendei et al., ), and schizophrenia (Peters, Hauschildt, Moritz, & Jelinek, ). The association between memory bias and psychiatric comorbidity is unclear at this point, but negative emotions are a key aspect of not only depression and anxiety, but of many psychiatric disorders (American Psychiatric Association, ).…”
Section: Introductionmentioning
confidence: 99%
“…Participants then rated their negative affect and the vividness of the memory recalled on a scale of 1-5. Trial-by-trial self-report is routinely used to evaluate regulatory success in healthy and clinical populations in the reappraisal literature (e.g., (Koenigsberg, Fan, 2009; Ochsner et al, 2002)) because moment-to-moment self-report is a more accurate means of assessing emotions than retrospective report (Stone and Shiffman, 1994) – particularly among individuals with BPD who may have memory distortions (Winter, Elzinga, 2014). After each trial, participants completed an active baseline task involving making button presses to indicate the direction of an arrow for 20 seconds (Stark and Squire, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The present study sought to do so using a paradigm that assessed emotion regulation for upsetting memories wherein participants were instructed on a trial-by-trial basis to either emotionally immerse or distance (i.e., reappraise) themselves from their memories. Upsetting memories were used both because they effectively elicit negative affect and are clinically significant (Winter et al, 2014). Three hypotheses were tested.…”
mentioning
confidence: 99%
“…Through extensive feedback loops to limbic structures, these prefrontal regions exercise a measure of “top-down” tonic control to maintain emotional homeostasis (Davidson and Irwin, 1999). In patients with BPD, affective interference, especially by negative stimuli, impairs functioning of brain networks that sub-serve cognitive processing of executive functions required for adaptive responding (Sebastian et al, 2013; Soloff et al, 2015; Winter et al, 2014). …”
Section: Introductionmentioning
confidence: 99%